Konsekwencje "rajdu Jamesona" dla stosunków brytyjsko-burskich (styczeń-kwiecień 1896 r.) - Damski, Przemysław Piotr (Acta Universitatis Lodziensis. Folia Historica, 2010)
Period between January and April 1896 in Boer-British relations was more specific than other ones. Great Britain stood in face of difficult situation because of “Jameson raid". British South African Company troops had invaded formally friendly state, which had serious economic bonds with German Empire and even developed friendly relations with it. In such case Britain’s most significant issue was to calm down the situation and to stress that South Africa was still area British of influence. That’s why secretary of state for the colonies - Joseph Chamberlain, was very careful relating to Transvaal and stressed that British Empire dissociated itself from the action of BSAC, and it would help in any way. On the other hand he aggressively react on Kruger Telegram. In 17th January 1896, some of British subjects inhabitants of Witwatersrand came up an idea in which president should visit to London to explain all misunderstandings, that had gathered long before the raid. Both sides were positive to this idea, but Chamberlain wanted only to explain all difficulties between Empire and its protectorate. Kruger had other vision. He demanded an invitation and promise that Article IV of London Convention 1884 would be changed. Secretary Chamberlain sent the invitation but he could not agree at president’s conditions as far as Convention was concerned. Finally at 27th April Kruger refused visit to London and Cabinet withdrew the invitation. The discussion over Article IV did not finish after Kruger’s withdrawal from the idea of presidential visit. Transvaal came out with its new interpretation. British rightly saw, that it might threat their interests, and they even might lose their suzerainty over South African Republic. Because of that they opposed the idea. Dispute was partly solved in 1898 by settlement which gave Transvaal more freedom in its international politics. The attitude of both sides was more and more uncompromising, and the zenith of it took place at Bloemfontein Conference at 1899.